Association between interleukin 6 -174 G/C promoter gene polymorphism and runners' responses to the dietary ingestion of antioxidant supplementation based on pequi (Caryocar brasiliense Camb.) oil : a before-after study - Miranda-Vilela, Ana Luisa (2016)
Exercise is a double-edged sword: when practiced in moderation, it increases the expression of antioxidant enzymes, but when practiced strenuously it causes oxidative stress and cell damage. In this context, polymorphisms in the interleukin (IL)-6 gene should be investigated better because they can influence performance, at least in exercise that generates oxidative stress and leads to muscular injuries with consequent inflammation. In this work, we investigated the influence of IL-6 –174 G/C polymorphism on tissue damage and inflammation markers, lipid peroxidation, hemogram and lipid profile of runners before and after ingestion of 400 mg of pequi oil in capsules supplied daily for 14 consecutive days. The IL-6 genotypes were associated with significant differences in lipid peroxidation, with the CC mutant having lower values. There were also significant differences among these genotypes in the response to supplementation with pequi oil, exercise-induced damage and C-reactive protein (CRP) levels. The best protection against damage was observed with the heterozygous genotype. Although the CC genotype showed an increase in CRP levels after supplementation, the lack of a positive correlation between triglycerides and high-sensitivity CRP in this mutant genotype after supplementation indicated a protective effect of pequi. These findings deserve further investigation, particularly with regard to the quantification of circulating IL-6 concentrations.